2009
DOI: 10.1016/j.autneu.2009.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exercise capacity and heart rate variability: Supine and in response to an orthostatic stressor

Abstract: A b s t r a c tThe study investigated whether supine-measured HRV indicators, and/or HRV indicators measured during orthostatic stress are related to conventional measures of exercise and performance ability such as VO 2max . Only two significant correlations (pb0.05) out of 30 tests were found between supinedetermined HRV indicators and conventional measures. In contrast, fifteen of the 30 relationships calculated during orthostatic stress were significant. Relationships were at best low to moderate (0.2b|cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
(21 reference statements)
1
13
0
2
Order By: Relevance
“…Another drawback is that the tachogram used to determine HRV, was sampled only in a resting, supine position. Previous studies indicated that HRV measured during a stressor, such as standing upright, show more significant correlations with cardiopulmonary fitness indicators than supine HRV measurements (Grant et al, 2009 ). For future studies it is recommended to investigate participants from other age groups as well as clinical groups to answer the question whether these results are only applicable to healthy young participants and if not; how it differs in other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Another drawback is that the tachogram used to determine HRV, was sampled only in a resting, supine position. Previous studies indicated that HRV measured during a stressor, such as standing upright, show more significant correlations with cardiopulmonary fitness indicators than supine HRV measurements (Grant et al, 2009 ). For future studies it is recommended to investigate participants from other age groups as well as clinical groups to answer the question whether these results are only applicable to healthy young participants and if not; how it differs in other groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the evaluation of autonomic regulation of the heart rate, which is indicated by its variability changes in response to an orthostatic challenge, has been suggested to predict an individual’s capacity for adaptive responses of the sympathetic nervous system (SNS) 4 5 6 7 8 9 10 11 . However, withdrawal of these adaptive changes or recovery after an orthostatic challenge should be considered an individual’s capacity for resilience or recovery status of the parasympathetic nervous system (PNS) 8 12 13 14 15 16 17 .…”
mentioning
confidence: 99%
“…Heart rate variability, referring to the changes in beat to beat heart rate measured over a period of a RR-interval recording (tachogram) [8,9], has been proven as a valid method to assess stress in humans [8] and animals [10], including horses [5,6,[11][12][13][14], pigs [15,16], sheep and goats [17][18][19], cattle [20,21], poultry [22], and dogs [23,24]. Studies in humans showed that standardization of methodology is important to assure inter-and intra-study repeatability of HRV measurements [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%